Peran Production Assistant News dalam Pengemasan Berita Harian YouTube Liputan 6 SCTV di PT Surya Citra Media Tbk - Abimanyu, Fitra Anggito; Melano, Fiqie Lavani (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
This study addresses the decreasing interest in traditional television viewing, prompting Liputan 6 SCTV to utilize YouTube as an information dissemination platform. The role of Production Assistant News is critical in creating engaging content to enhance audience engagement on the Liputan 6 SCTV YouTube channel. The objective of this study is to explore how Production Assistant News contributes to increasing audience interaction and engagement. Using a descriptive qualitative research method, data were collected through observations, interviews, documentation, and literature reviews. The findings reveal that Production Assistant News plays a significant role in producing compelling Video on Demand (VOD) content, which leads to increased public preference for Liputan 6 SCTV as an information source. The successful implementation of this role is evidenced by a notable rise in subscribers, viewers, likes, and engagement metrics, as recorded by YouTube Studio.